2012
DOI: 10.5430/jst.v2n1p22
|View full text |Cite
|
Sign up to set email alerts
|

Right hand digit ratio (2D:4D) is associated with prostate cancer: Findings of an admixed population study

Abstract: Objective: Digit ratios are considered putative markers for prenatal hormone exposure, as well as the action of HOX and AR genes. Such genes have been connected to carcinogenesis and digit ratio could help to identify patients that bear such predisposition. The purpose of this study was to investigate the possible correlations between digit ratio, prostate cancer (PCA) -the most common cancer in men -and benign prostate hyperplasia (BPH) in a multiethnic sample of men between 50 and 80 years, the main risk gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…In contrast to our study, many studies have looked at only the 2D: 4D finger ratio of the right hand (Hopp & Jorge, ; Jung et al, ; Rahman et al, ; Waters et al, ), considering that the 2D:4D finger ratio of the right hand shows prenatal androgenic exposure better than the left hand (Hönekopp & Watson, ). In our study, there was a negative correlation between finger ratios and prostate volumes only in right hand.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In contrast to our study, many studies have looked at only the 2D: 4D finger ratio of the right hand (Hopp & Jorge, ; Jung et al, ; Rahman et al, ; Waters et al, ), considering that the 2D:4D finger ratio of the right hand shows prenatal androgenic exposure better than the left hand (Hönekopp & Watson, ). In our study, there was a negative correlation between finger ratios and prostate volumes only in right hand.…”
Section: Discussioncontrasting
confidence: 57%
“…4D finger ratio of the right hand (Hopp & Jorge, 2012;Jung et al, 2011;Rahman et al, 2011;Waters et al, 2013), considering that the 2D:4D…”
Section: Discussionmentioning
confidence: 99%
“…A smaller but much admixed population was analyzed in Brazil for prostate cancer prevalence, and compared to a sample of benign prostatic hyperplasia (BPH). 10 Once again, only right-hands were evaluated and males with prostate cancer presented lower digit ratios than the ones with no prostatic lesions. The authors suggested 2D:4D as a possible screening marker for prostate cancer incidence.…”
Section: Prostate Cancermentioning
confidence: 99%